Comparative Analysis of Photosensitizer Penetration Depth in Root Canal Debridement for Endodontic Disinfection - sharifzadeh, Seyedeh Saba; Gerami Amin, Mehrnaz; Moezzi Ghadim, Nahid; Fazlyab, Mahta; Azizi, Arash (Iranian Endodontic Journal, 2024)
Introduction: Microbial agents play a crucial role in periapical lesions and despite mechanical preparation, presence of persistent bacteria in root canal system is a challenge. Photodynamic therapy offers a debridement method, utilizing photosensitizers such as Curcumin, Indocyanine Green (ICG), and Methylene Blue (MB). This study aimed to assess and compare the penetration depth of these photosensitizers on the lateral surface of the root canal. Materials and Methods: The crown of 30 single-rooted teeth were separated by a diamond disc. The canals were prepared using a rotary system and were rinsed with 10 mL of 2.5% NaOCl. In order to remove the smear layer debris, 17% EDTA was placed in the root canal for 1 min, then rinsed with NaOCl and saline. The teeth were sterilized by autoclave and randomly assigned to three groups that filled with curcumin, ICG, or MB. Subsequently, they were incubated for 10 min and dried up by paper. Longitudinal sections were cut, and penetration depth of the photosensitizers in coronal, middle, and apical sections were measured using a stereomicroscope. Results: Curcumin demonstrated a higher average penetration depth (3000 µm) than MB, and MB showed higher penetration depth than ICG. Significantly different penetration depths were observed in pairwise comparisons among all three groups (P<0.005). Conclusion: Curcumin with its superior average penetration depth, emerges as a promising choice for effective root canal disinfection in endodontic treatments. Consideration of these findings may enhance the selection of photosensitizers in clinical applications.